Active nickel hollow nanosphere supported over SiO2 catalyst for reduction of nitro compound - Pawar, Priyanka S.; Lokhande, Aboli A.; Nandanwar, Sachin U.; Niphadkar, Prashant S.; Bokade, Vijay V. (Particulate Science and Technology, 2021)
Nickel hollow nanospheres (Ni HNSs) was prepared by solvothermal method using mixture of ethylenediamine (EN) and ethanol (ET), sodium borohydride as reducing agent and nickel chloride hexahydrate as precursor. The particle size of the Ni HNSs were tuned by varying several parameters including precursor concentrations, reaction temperatures (130-190 degrees C), and ET to EN volume ratios. The particle size and morphology of Ni HNSs were confirmed by dynamic light scattering and transmission electron microscope, respectively. Spherical shape of Ni nanoparticles of 300 nm size having similar to 200 nm hollow space and 50 nm thickness was achieved at optimize condition of 4:6 volume ratio of ET/EN, 150 degrees C temperature, 0.1 M NaBH4 concentration, and 7 h. Ni HNSs supported over SiO2 (Ni HNSs/SiO2) with different loading of Ni HNSs (1-10 wt.%) were prepared by impregnation method. The catalyst was characterized by X-ray diffraction, and inductively coupled plasma - optical emission spectroscopy. The catalytic performance of Ni HNSs/SiO2 was carried out in the reduction of 4-Nitrophenol (4-NP) to 4 - Aminophenol (4-AP). 5 wt.% Ni HNSs/SiO2 exhibited 87% reduction of 4-NP in 25 min and stable up to 6 catalyst cycles due to higher surface area of the catalyst.
Keywords: 4-Aminophenol; 4-nitrophenol; Catalyst; hollow nanospheres; Nanoparticles; Nickel